Mechanisms of induction of β-carotene accumulation in microalgae Dunaliella salina cells with nitrogen starvation - Samovich, Tatsiana V.; Svechko, Alexei D.; Kozel, Nikolay V. (Experimental Biology and Biotechnology, 2026)
It has been shown that conditions of nitrogen starvation and exposure to high intensity light significantly affect the pigment composition of cells of microalgae Dunaliella salina (strain IBCE D-1) during its cultivation. In particular, there is a decrease of the concentration of chlorophyll and neoxanthine by 7 times, violaxanthin by 5, lutein by 4 times against the background of an increase of the concentration of β-carotene in the cells of microalgae by 6 times. The combined eﬀect of nitrogen starvation and high intensity light is the most eﬀective of the methods studied in the work to increase the production of β-carotene by cells of D. salina. A decrease in the D1 protein amount of the reaction centre of photosystem II and a predominant activity suppression of this photosystem in the cells of microalgae cultivated in a nitrogen-deficient medium was found, which may be a key factor in increased synthesis of β-carotene.
Keywords: microalgae; Dunaliella salina; β-carotene; photosynthetic apparatus; nitrogen starvation